Acute myocardial infarction at an early age – importance of acute chest pain fast track in patient management. (14th October 2021) - Carvalho, D; Bastos, J M; Viegas, V; Pacheco, A; Ferraz, L; Carvalho, P; Ferreira, R; Neves, A B
Abstract: Background: Acute coronary syndrome (ACS) has a higher incidence in middle-aged and elderly patients but 2% to 6% of ACS cases occur in people younger than 45 years of age (Y). Younger patients have different clinical characteristics when compared to older patients. Acute chest pain fast track led to a reduction in the time required for the diagnosis of acute coronary syndromes, particularly those with ST segment elevation (STEMI). Aim: This study aims to assess the differences in risk factors and clinical characteristics between young and older ACS patients. Besides that, we try to determine if the benefits of acute chest pain fast track have extended to this younger population. Material and methods: Retrospective observational study carried out through the analysis of the clinical process. Clinical data were collected from ACS patients under 45Y from 2010 to 2019 and from ACS patients over 45Y from 2010 to 2012. Statistical analysis was made using R software and RStudio. Results: This study included 93 patients with ACS under 45Y and 172 patients with ACS over 45Y. A total of 265 patients were included. The male gender was predominant in both groups but with a higher prevalence in the younger ones (88% vs 73%, p<0, 005). The prevalence of hypertension was higher in older ACS patients but the younger ones had more overweight (39.8% vs 17.4%, p<0, 001), smoking history (84.9% vs 38.4%, p<0, 001) and family history of sudden death (25.8% vs 5.8%, p<0, 01). Diabetes had no statistical difference. Dyslipidemia as previous known risk factor had no statistical difference but LDL was higher in patients with less than 45Y (147.2 vs 120.7 mg/dL, p<0, 001). STEMI were tendentially more prevalent in patients under 45Y (55.9% vs 44.8%, p 0.09). The anterior wall was the most frequently involved in both groups (52% vs 63%, p 0.28), followed by the inferior wall (42% vs 36%). Accordantly, anterior descending artery was the artery most frequently involved in both groups (44.1% vs 48.3%), followed by right coronary artery (24.7 vs 26.7%). STEMI patients under 45Y were submitted to an emergent coronary angiography in 89% of cases and STEMI patients over than 45Y were submitted in 70.1% of cases. Particularly for patients under 45Y, all STEMI patients were submitted to an emergent coronary angiography after 2014, which emphasis the importance of acute chest pain fast track in the emergency room. Finally, ACS patients under 45Y were less submitted to percutaneous coronary angiography compared to patients over 45Y (15.1% vs 4.7%, p<0, 001). Conclusions: Cardiovascular risk factors differ accordingly the age of ACS patients. Younger patients had more overweight and smoking history. They probably have alternative pathophysiologic mechanisms that explain differences in percutaneous coronary angiography. Acute chest pain fast track had an important role reducing morbimortality related to ACS by reducing the time until STEMI diagnose. Funding Acknowledgement: Type of funding sources: None.